Clinical outcomes and structural integrity rate of arthroscopic augmented rotator cuff repairs using extracellular porcine matrix patch. (July 2022) - Consigliere, Paolo; Bernasconi, Alessio; Dimock, Richard; Narvani, A Ali
Background: Structural failure rate in rotator cuff repairs is still high. The purpose of the study is to assess the structural integrity of a series of augmented rotator cuff repairs with porcine matrix patch and report the functional outcomes. Methods: Between 2014 and 2017, 44 consecutive patients underwent arthroscopic double-row repair of medium to massive rotator cuff tears with extracellular porcine dermal matrix augmentation. At one-year follow-up, magnetic resonance imaging scan was performed to assess the integrity of the repair. Oxford Shoulder Score (OSS), Constant Score (CS) and Visual Analogue Scale pain score, together with range of motion were used to assess patients. Results: Patients mean age was 68 (53–82); mean follow-up was 17.2 (12–24) months. On magnetic resonance imaging scans, seven rotator cuff repair failures (15.9%) were observed: tear size was an independent predictor of re-rupture at one-year follow-up. Clinical scores showed a statistically significant improvement at three months and until final follow-up ( p < 0.001). No complications occurred. Conclusion: Observed structural failure rate of 15.9% is lower than those reported in the literature for standard rotator cuff repair of medium to massive tears in similar cohorts to ours. Extracellular matrix augmentation for rotator cuff repair was shown to be a safe and reliable support to the repairs and patients recovered good shoulder function. Level of Evidence: Level IV.